Product market structure and monetary policy: Evidence from the euro area - Annalisa Ferrando; Peter McAdam; Filippos Petroulakis; Xavier Vives (European Central Bank (ECB), 2021)
Monetary policy aims at affecting corporate borrowing by influencing the marginal costs of firms, but its potency can be conditioned by the degree of market competition. We first identify conditions under which changes in marginal costs may have different effects on credit constraints and output under different competitive environment, in a simple Cournot competition setting. We then exploit changes in monetary policy to examine whether the pass-through of borrowing costs is affected by market structure. First, we use as an experiment the announcement of the ECB Outright Monetary Transactions (OMT) program in a triple-differences specification. We show that small firms (which have low market power and higher credit constraints) in "stressed" countries (which benefited more from the policy) within less concentrated sectors experienced a larger reduction in credit constraints than similar firms in more concentrated sectors. Second, we exploit continuous state-of-the-art measures of monetary policy shocks to study how market structure affects pass-through to real variables, like investment and sales growth. We find evidence that firms with more market power respond less to monetary policy shocks. These results show that the interaction of borrowing capacity and market structure matters, and that concentration may have important effects on monetary policy transmission.
Keywords: D4; E4; E5; L1; 330; Monetary Transmission; OMT; Marginal Costs; Competition; Credit Constraints